2013
DOI: 10.1371/journal.pone.0079324
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Cross-Over Trial of the Postprandial Effects of Three Different Diets in Patients with Type 2 Diabetes

Abstract: BackgroundIn the clinic setting both fasting levels of glucose and the area under the curve (AUC) of glucose, by determination of HbA1c levels, are used for risk assessments, in type 2 diabetes (NIDDM). However little is known about postprandial levels, and hence AUC, regarding other traditional risk factors such as insulin and blood-lipids and how this is affected by different diets.ObjectiveTo study postprandial effects of three diets, during a single day, in NIDDM.MethodsA low-fat diet (45–56 energy-% from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 36 publications
1
33
0
4
Order By: Relevance
“…It has been hypothesized that lower postprandial glucose excursion on a low-carbohydrate, high-fat (LCHF) diet may lead to a better glucose control [7,8]. LCHF diets have been promoted as a possible strategy for the management and prevention of T2DM, but there is no consensus on the best macronutrient composition [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that lower postprandial glucose excursion on a low-carbohydrate, high-fat (LCHF) diet may lead to a better glucose control [7,8]. LCHF diets have been promoted as a possible strategy for the management and prevention of T2DM, but there is no consensus on the best macronutrient composition [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, os autores concluíram que existem efeitos benéficos em ambas as dietas oferecidas, embora estes tenham sido mais pronunciados nos indivíduos portadores de DM tipo II que receberam a dieta LC. Fernemark et al (2013), compararam por meio de um estudo cruzado e randomizado, uma dieta com baixo teor de gordura (45-56% de energia vinda dos carboidratos), e uma dieta LC (16-24% de energia vinda dos carboidratos), com uma dieta de estilo mediterrâneo. Dos 21 pacientes portadores de DM tipo II inicialmente recrutados, 19 completaram o estudo.…”
Section: Revisão Da Literaturaunclassified
“…The optimal amount of wine appeared to be approximately two drinks/day, where a standard drink in Australia is considered to be 10 g alcohol [34]. Wine consumed with food, and especially as an integral component of Mediterranean-type diet, was inversely associated with type 2 diabetes mellitus [35][36][37]. The inverse association was particularly observed for overweight and obese individuals at higher risk of developing the disease [32,33,35], in middle-aged individuals [17,38] and in elderly individuals [30,39].…”
Section: Wine and Diabetesmentioning
confidence: 99%
“…Micro-vascular and other complications of type 2 diabetes mellitus were also inversely associated with regular moderate wine consumption [24,29,36,[45][46][47][48][49][50]. Beulens et al (2010) [48], for example, suggested that one to two drinks/day as wine was associated with a reduced risk of vascular-related deaths such as from coronary heart disease, myocardial infarction and stroke as well as non-fatal events including amputations in diabetic individuals at high risk of cardiovascular disease compared to abstainers.…”
Section: Wine and Diabetesmentioning
confidence: 99%